The Impact of Moral Education on Religious Life - Shamshiri, Mohammad Reza (Journal of History Culture and Art Research, 2017)
Moral education is the foundation of happiness and misery of human beings and societies. Thus, the present study explores the necessity of moral education in life and its impact on the realization of Islamic lifestyle using descriptive-analytical method. Without morality, religion has no meaning for people, and the world will not be organized. The issues of ethics, self-purification, and be adorned with moral virtues are of utmost importance in all monotheistic religions, especially in Islam. Man is capable of connecting to all perfections but achieving it depends on the correct training, and in order to achieve the grand aim of closeness to God, the best practice should be chosen. In the Islamic tradition, the aim is gaining the satisfaction of God. In addition, the governed relations on the individuals' lives are affected by the perspective inspired by lifestyle. Thus, the effect of moral education to establish Islamic lifestyle is undeniable and inevitable.